Wireless and configurationless iClassroom system with remote database via Bonjour - M. A., Ameedeen; Zafril Rizal, M Azmi (Springer Nature Switzerland, 2012)
Wireless communication protocols are fast replacing wired communication methods in the world nowadays, especially with the ever-growing popularity of mobile devices. One such wireless communication protocol that has a unique characteristic of not requiring any sort of configuration is Bonjour, an Apple proprietary zero-configuration protocol that are currently used in Apple manufactured devices such as the Apple MacBook, iPads and iPhones. This paper aims to utilize this unique wireless communication protocol in an intelligent classroom environment (iClassroom) where the teachers and students communicate wirelessly using their mobile devices through the iClassroom system that requires no configuration.